Carboidrases em dietas de leitões na creche: revisão sistemática e meta-análise - Silva, Julia de Camargo da (2022)
The objective of this meta-analysis was to evaluate the effects of multi-carbohydrases, having non-starch polysaccharides (NSP) as substrate, on the total tract digestibility of diets and performance of piglets, in the nursery phase. Initially, a search was carried out on research platforms (PubMed, Science Direct, Scielo and Web of Science) using the keywords: “carbohydrase”, “piglets”, “performance” and “digestibility”. A total of 254 articles were found, of which 26 met the eligibility criteria and resulted in 56 studies considered. The digestibility variables were dry matter (DM), gross energy (GE), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF). In the performance evaluation, the average daily feed intake (ADFI), average daily gain (ADG) and feed conversion (FC) were considered. The data were analyzed for the effect of the addition of carbohydrases on the variables of interest, using the effect size (ES) method, with a confidence interval of 95%. Meta-regression analyzes were also performed to investigate the effect of the covariates total non-starch polysaccharides (NSPTT), soluble non-starch polysaccharides (NSPsol) and insoluble non-starch polysaccharides (NSPINS) on the effect of carbohydrates on the variables analyzed. The performance results were analyzed by periods, according to the experimental duration of the studies: 1 to 7 days (P1), 8 to 14 days (P2), 15 to 21 days (P3); 22 to 28 days (P4), 29 to 42 days (P5) and total period (PTOTAL – 1 to 42 days). Data analysis indicated that the use of multi-carbohydrases increases the digestibility of DM, DM and CP. Higher ADG (P<0.05) was observed in piglets that received enzyme supplementation, except in P5 and P6. The multi-carbohydrases influenced the FC of piglets at P2 (ES = 0.131 (0.018.0.245); P = 0.023). Meta-regression analyzes indicated that the consumption of NSPTT, NSPINS and NSPSOL influence the enzymatic action in the CR during P1, P3 and PTOTAL (NSPTT, ES= 1.05-3.75x, P=0.023; NSPINS, ES = 0.99-4.24x, P=0.038; NSPSOL, ES=1.14-22.68x, P=0.004). In the ADG, there was an effect on P3 and P5 (NSPTT, ES = 0.22+1.17x, P = 0.007; NSPINS, ES = 0.21+1.40x, P = 0.005; NSPSOL, ES = 0.24+6.49x, P = 0.036). Therefore, it is concluded that carbohydrases influence the weight gain and feed conversion of piglets in the nursery phase, due to the increase in the total digestibility of dry matter, crude protein, and crude energy.